The Mediterranean Decision Support System for Marine Safety dedicated to oil slicks predictions. (November 2016) - Zodiatis, G.; De Dominicis, M.; Perivoliotis, L.; Radhakrishnan, H.; Georgoudis, E.; Sotillo, M.; Lardner, R.W.; Krokos, G.; Bruciaferri, D.; Clementi, E.; Guarnieri, A.; Ribotti, A.; et al.
Abstract: In the Mediterranean sea the risk from oil spill pollution is high due to the heavy traffic of merchant vessels for transporting oil and gas, especially after the recent enlargement of the Suez canal and to the increasing coastal and offshore installations related to the oil industry in general. The basic response to major oil spills includes different measures and equipment. However, in order to strengthen the maritime safety related to oil spill pollution in the Mediterranean and to assist the response agencies, a multi-model oil spill prediction service has been set up, known as MEDESS-4MS (Mediterranean Decision Support System for Marine Safety). The concept behind the MEDESS-4MS service is the integration of the existing national ocean forecasting systems in the region with the Copernicus Marine Environmental Monitoring Service (CMEMS) and their interconnection, through a dedicated network data repository, facilitating access to all these data and to the data from the oil spill monitoring platforms, including the satellite data ones, with the well established oil spill models in the region. The MEDESS-4MS offer a range of service scenarios, multi-model data access and interactive capabilities to suite the needs of REMPEC (Regional Marine Pollution Emergency Response Centre for the Mediterranean Sea) and EMSA-CSN (European Maritime Safety Agency-CleanseaNet).